Paleolithic and Mediterranean Diet Pattern Scores Are Inversely Associated with Biomarkers of Inflammation and Oxidative Balance in Adults. Issue 6 (20th April 2016) - Whalen, Kristine A; McCullough, Marjorie L; Flanders, W Dana; Hartman, Terryl J; Judd, Suzanne; Bostick, Roberd M
Abstract: Background: Chronic inflammation and oxidative balance are associated with poor diet quality and risk of cancer and other chronic diseases. A diet–inflammation/oxidative balance association may relate to evolutionary discordance. Objective: We investigated associations between 2 diet pattern scores, the Paleolithic and the Mediterranean, and circulating concentrations of 2 related biomarkers, high-sensitivity C-reactive protein (hsCRP), an acute inflammatory protein, and F2 -isoprostane, a reliable marker of in vivo lipid peroxidation. Methods: In a pooled cross-sectional study of 30- to 74-y-old men and women in an elective outpatient colonoscopy population ( n = 646), we created diet scores from responses on Willett food-frequency questionnaires and measured plasma hsCRP and F2 -isoprostane concentrations by ELISA and gas chromatography–mass spectrometry, respectively. Both diet scores were calculated and categorized into quintiles, and their associations with biomarker concentrations were estimated with the use of general linear models to calculate and compare adjusted geometric means, and via unconditional ordinal logistic regression. Results: There were statistically significant trends for decreasing geometric mean plasma hsCRP and F2 -isoprostane concentrations with increasing quintiles of the Paleolithic and Mediterranean diet scores. The multivariable-adjusted ORs comparing those in the highest with those in the lowest quintiles of the Paleolithic and Mediterranean diet scores were 0.61 (95% CI: 0.36, 1.05; P -trend = 0.06) and 0.71 (95% CI: 0.42, 1.20; P -trend = 0.01), respectively, for a higher hsCRP concentration, and 0.51 (95% CI: 0.27, 0.95; P -trend 0.01) and 0.39 (95% CI: 0.21, 0.73; P -trend = 0.01), respectively, for a higher F2 -isoprostane concentration. Conclusion: These findings suggest that diets that are more Paleolithic- or Mediterranean-like may be associated with lower levels of systemic inflammation and oxidative stress in humans.